Pergeseran Fungsi dan Makna Simbolis Kain Sasirangan - Yunita Fitra Andriana (JURNAL RUPA, 2018)
Sasirangan cloth is a result of the cultural work of the Banjar people in South Kalimantan, it has its own beauty, characteristics and uniqueness, both in terms of manufacturing techniques, colors, motifs and symbolical meanings. The symbolical meaning that contained in Sasirangan is closely related to its traditional motifs and the natural dyes which it has been used for many years. However, along with the current development, Sasirangan now has changed from using natural dyes to using synthetic dyes, so that the symbolical meaning needs to be reexamined. This study of shifting symbolical meanings of Sasirangan cloth uses qualitative methods with literature studies and analysis. The results of this study can be a reference source for studies related to Sasirangan cloth in particular, and traditional Indonesian fabrics in general.